Multiscale Biomimetic Evaporators Based on Liquid Metal/Polyacrylonitrile Composite Fibers for Highly Efficient Solar Steam Generation - Yuxuan Sun; Dan Liu; Fei Zhang; Xiaobo Gao; Jie Xue; Qingbin Zheng (Nano-Micro Letters)
Highlights A three-dimensional multiscale liquid metal/polyacrylonitrile evaporator is fabricated through wet spinning and assembly. The evaporator exhibits an outstanding water evaporation rate of 2.66 kg m−2 h−1 with a solar energy efficiency of 96.5% under one sun irradiation. The evaporator demonstrates a superior purification performance for seawater and sewage under light irradiation.